Lykke i ulykkens tid - Thomsen, Torsten Bøgh (K&K - Kultur og Klasse, 2016)
Taking its point of departure in two contemporary Danish poets, Victor Boy Lindholm and Theis Ørntoft, the article discusses affective poetic responses to the climate crisis. The concepts of ‘eco-mourning’ and ‘climate-melancholia’ are examined in order to deliberate the possibility for human happiness in late modernism. Poems by the writers are analysed with Sara Ahmed’s theories on happiness and perspectives from posthumanist theory (Cary Wolfe) and Timothy Morton’s notion of dark ecology. It is argued that the teleology, autonomy and futurism that, according to Ahmed, is inherent to the promise of happiness, is rendered impossible by the climate crisis and accordingly problematized stylistically in some works of climate poetry. This leads to a discussion of the poetry of Lindholm and Ørntoft in relation to Freud’s theory on mourning and melancholia, which ends by concluding that Lindholm’s poetry can be seen as representative of a mourning that reproduces dynamics of desire in a dialectical oscillation between optimism and pessimism. In contrast, Ørntoft’s poetry marks a melancholy dispensation of the structures that this desire works within. The conclusion is that in an age of climate crisis, mourning can be seen as a problematic speculation in future and continuation of the structures of happiness and desire that produced the crisis to begin with, whereas melancholia is a mental mode that brackets out such dialectical thinking and promises of future happiness.